Efeitos da estimulação transcraniana por corrente contínua nos sintomas de ansiedade social - Sousa, Gleiciano Rodrigo Morais de (2020)
Social anxiety disorder (SAD) is defined as a persistent fear or anxiety in one or more social situations in which the individual can be judged by others. It tends to start in childhood, shows a high level of comorbidities and is often confused with shyness, which is why it requires effective methods of evaluation and diagnosis. Although traditional treatments are effective, some patients with SAD are refractory, therefore, the search for new treatments is necessary. Transcranial direct current stimulation (tDCS) is a potential alternative whose clinical efficacy in psychiatric disorders is being studied. Thereby, this work aimed to develop two studies to assist in the investigation about the effects of tDCS from the ventromedial prefrontal cortex (vmPFC) on social anxiety. For this purpose, two articles were elaborated to compose the research, the first article was the development of a standardized tDCS intervention protocol in people with social anxiety, and the second was a case report that evaluated the effect and reliability of tDCS on the symptoms of social anxiety in a patient. For the development of the protocol, a review of the neuroimaging studies of the disorder and of those that used tDCS in patients with SAD was performed. In the second study, a protocol of five sessions with the duration of 20 minutes using tDCS at 2mA of intensity, with anodic and cathodic electrodes positioned in the left and right vmPFC respectively, was tested on a 25 year old female patient. As measures in the pre and post intervention, the Liebowitz Social Anxiety Scale, the Social Phobia Inventory, and the evaluation of heart rate variability under exposure to a behavioral task in virtual reality were used. As results of the first study, the development of the protocol was obtained, the results from the case report were positive, when considering the clinically observed reduction in anxiety symptoms in the patient, but further research is needed to analyze the external accuracy of the results. Protocol articles serve as a guide for future research, and in this work, it was possible to test the accuracy of the protocol developed from the case report. Works of this nature represent an important step towards understanding the therapeutic effects of tDCS and its adverse effects, and can assist researchers, health professionals and patients in understanding the neurophysiology of SAD.